A study of the influence of crystal component on the reactivity of low-calcium fly ash in alkaline conditions based on SEM-EDS. (20th May 2020) - Wang, Tiao; Ishida, Tetsuya; Gu, Rui
Highlights: An approach was developed to characterise low-calcium fly ash based on SEM-EDS. The content of mullite affects the reactivity of Al-silicate glass. The content of mullite is proportionate to undissolved content of fly ash. Mullite exists as a small solid that is widely distributed in Al-silicate glass. Quartz tends to exist alongside and is usually covered by silicate glass. Abstract: The use of fly ash to improve concrete performance has increased around the world in recent decades. However, the engineering application of fly ash remains limited by its heterogeneity and variability. This paper presents a developed approach for comprehensive characterisation of fly ash material properties based on scanning electron microscopy–energy-dispersive X-ray spectroscopy full-element mapping with image analysis. The chemical compositions, mineralogical and amorphous phase assemblage and specific surface area of each phase can be visually analysed and quantified. Analysis reveals that the phase assemblage of fly ash is affected by its combustion conditions. Although a wide distribution of crystalline mullite can be found in fly ash particles, crystalline quartz is usually covered by amorphous silicate. The characterisation approach developed in this study is used to investigate the influence of crystal components on kinetic properties of various phases of fly ash in alkaline conditions. The results show that crystalline mullite affects the kinetic properties of Al-silicate glass and glass-mullite intermixtures.